Analysis of risk factors for hospital-acquired pneumonia in schizophrenia - Chen, Yu-hang; Ren, Cong-ying; Liao, Yu (Frontiers in Psychiatry, 2024)
Background: Hospital-acquired pneumonia is one of the most important causes of recurrent illness, disease progression, and even death during hospitalization. Patients with schizophrenia have the special characteristics of their disease, and at the same time, the occurrence of hospital-acquired pneumonia is more common among patients with schizophrenia due to the prolonged stay in closed wards, accompanied by various factors such as age, gender, and nutritional status.Methods: The PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), and China Biomedical Literature Database (CBM) databases were searched with a timeframe of build to February 2024 to collect studies on factors influencing hospital-acquired pneumonia in patients with schizophrenia. Two researchers independently screened the literature, extracted data, and analyzed them.Results: A total of 5 papers including 85246 patients were included in the literature, which suggested that benzodiazepines (especially the use of clozapine), combination of antipsychotics, mood stabilizers, modified electroconvulsive therapy (MECT), duration of hospitalization, underlying diseases, hyperglycemia, and salivation/dysphagia were important risk factors for hospital-acquired pneumonia in schizophrenia patients, and that advanced age, smoking and alcohol drinking Older age, smoking and drinking habits, malnutrition, and underlying diseases are also risk factors for hospital-acquired pneumonia.Conclusions: Patients with schizophrenia are at a higher risk of developing hospital-acquired pneumonia, so identifying the risk factors associated with hospital-acquired pneumonia and evaluating them comprehensively and promptly during hospitalization facilitates the development of early interventions, which are essential for improving the prognosis of patients with schizophrenia.